DISKURSUS KETUHANAN DALAM PUSTAKA BRAHMAVIDYA-UPANISAD HASIL TRANSLITERASI OLEH BEBERAPA SARJANA BARAT DAN TIMUR - Donder, I Ketut (PANGKAJA: JURNAL AGAMA HINDU, 2021)
Divinity discourse in the Vedas is very broad, so that it gave birth to many documents from the results of reflection and in-depth study of the search for God. This Brahmavidya-Upanisad is the centerpiece of the 39th Upanisad of 112 Upanisads translated by board scholars. This Brahmavidya-Upanisad is the result of contemplative research by ancient sages who used the paravidya-apaparavidya approach. This approach is a holistic approach, namely the paravidya approach is related to the investigation of the microcosm, and the aparavidya approach is related to the investigation of the macrocosm. The paravidya approach is a spiritual approach (subjective) and the aparavidya approach is a material approach (positive objective). The integration of this positivistic subjective-objective approach is a harmonious-integrative approach called a holistic approach, a blend of spirituality and science. The results of integrative contemplative research on the combination of spiritual-science found that the macrocosm and micro-cosm are the same but differ in intensity.The results of the research of these sages have given space for mankind to seek God within themselves or to seek God in all of His creations that are in front of humans. There is nothing worse or better than man's search for God. If he is a layman then he can seek and place God outside of himself; but for spiritualists can worship God inside or outside themselves or both. This is a form of theology of freedom and theology of liberation that can liberate humans from alienation from God.